Lupane and 18α-oleanane derivatives substituted in the position 2, their cytotoxicity and influence on cancer cells - Borkova, Lucie; Gurska, Sona; Dzubak, Petr; Burianova, Renata; Hajduch, Marian; Sarek, Jan; Popa, Igor; Urban, Milan (European journal of medicinal chemistry, 2016)
Lupane derivatives containing an electronegative substituent in the position 2 of the skeleton are often cytotoxic, however, the most active compounds are not selective enough. To further study the influence of a substituent in the position 2 in lupane and 18α-oleanane derivatives on their biological properties, we prepared a set of 38 triterpenoid compounds, 19 of them new, most of them substituted in the position 2. From betulin, we obtained 2-bromo dihydrobetulonic acid and 2-bromo allobetulon and their substitutions yielded derivatives with various substituents in the position 2 such as amines, amides, thiols, and thioethers. Nitration of allobetulon and dihydrobetulonic acid gave 2-nitro and 2,2-dinitro derivatives. Fifteen derivatives had IC50 < 50 μM on a chemosensitive CCRF-CEM (acute lymphoblastic leukemia) cell line and were tested on another seven cancer cell lines including resistant and two non-cancer lines. 2-Amino allobetulin had IC50 4.6 μM and caused significant block of the tumor cells in S and slightly in G2/M transition and caused strong inhibition of DNA and RNA synthesis at 5 × IC50. 2-Amino allobetulin is the most active derivative of 18α-oleanane skeletal type prepared in our research group to date.
Keywords: kyselina olenalová; Inhibitory Concentration 50; Cell Line, Tumor; screeningové testy protinádorových léčiv; lidé; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; Antineoplastic Agents; protinádorové látky; inhibiční koncentrace 50; nukleové kyseliny; Cytotoxins; Nucleic Acids; triterpeny; cytotoxiny; Oleanolic Acid; Drug Screening Assays, Antitumor; Triterpenes; nádorové buněčné linie; Humans